DIFFERENT LOOKS AT TWO PEDAGOGICAL CONFERENCES: CUBA (1884 ) AND CENTRAL AMERICA (1893) - Nivón Bolán, Amalia (2014)
The pedagogical congresses of the nineteenth century held in Cuba and Guatemala, have involved faculty and staff related with education policy for primary education, interested in retrofitting public education to the conditions of the time in these two countries, in a context of independence and abolitionists, centralists and federalists mobilizations that took place the last 25 years of this century in different countries of Latin America. Some characteristics that are the basis for understanding the dynamics that favored the reorganization of the education system of public elementary schools, in terms of content and teaching methods, profiles of teachers and training for new generations are identified; all in particular economic and political contexts, where groups of intellectuals linked to articulately state participated in institutional education projects. The literature review is based on the electronic memory of the First Pedagogical Centroamerican Congress, current historical research and biographical dictionaries.